2017
DOI: 10.1057/s41303-016-0029-7
|View full text |Cite
|
Sign up to set email alerts
|

Information quality, user satisfaction, and the manifestation of workarounds: a qualitative and quantitative study of enterprise content management system users

Abstract: In this paper, we focus on a critical aspect of work in organizations: using information in work tasks which is provided by information systems (IS) such as enterprise content management (ECM) systems. Our study based on the IS success model, 34 interviews, and an empirical study of 247 ECM system users at a financial service provider indicates that it is appropriate to differentiate between contextual and representational information quality as two information quality dimensions. Furthermore, we reveal that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 83 publications
5
100
0
4
Order By: Relevance
“…But we also need more quantitative research to measure and further theorize workarounds' causes and consequences and workaround behaviors. Of all the studies in the review, only Laumer et al (2017) used quantitative methods. Since workaround behaviors can take different forms in different settings, we need to understand the context and phenomena before using quantitative data-collection methods, which makes studying workarounds ideal for multi-method research that combines qualitative and quantitative methods (Venkatesh, Brown, & Bala, 2013;Ågerfalk, 2013 surveys and system data could provide data that could strengthen or contradict existing findings and provide new theories that researchers can further explore using qualitative methods.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…But we also need more quantitative research to measure and further theorize workarounds' causes and consequences and workaround behaviors. Of all the studies in the review, only Laumer et al (2017) used quantitative methods. Since workaround behaviors can take different forms in different settings, we need to understand the context and phenomena before using quantitative data-collection methods, which makes studying workarounds ideal for multi-method research that combines qualitative and quantitative methods (Venkatesh, Brown, & Bala, 2013;Ågerfalk, 2013 surveys and system data could provide data that could strengthen or contradict existing findings and provide new theories that researchers can further explore using qualitative methods.…”
Section: Discussionmentioning
confidence: 99%
“…Laumer, Maier, and Weitzel (2017) extended the IS success model (DeLone & McLean, 1992 with workarounds as a construct and concluded that user satisfaction negatively relates to workarounds and that both system quality and information quality play an important role in determining user satisfaction. Laumer et al (2017) also concluded that workarounds negatively relate to net benefit. Parks et al (2017) developed the unintended consequences of privacy safeguard enactment (UCPSE) framework to explain how individuals evaluate the consequences that may arise from enacting privacy safeguards.…”
Section: Theorizing Workaroundsmentioning
confidence: 99%
See 3 more Smart Citations